Possibilities of Archaeological Prospection by High‐resolution X‐band Satellite Radar – a Case Study from Syria. Issue 2 (6th May 2013) - Linck, R.; Busche, T.; Buckreuss, S.; Fassbinder, J. W. E.; Seren, S.; Lasaponara, Rosa; Masini, Nicola
ABSTRACT The launch of the first German radar satellite TerraSAR‐X in 2007 opened a new era in spaceborne radar remote sensing. So far the applicability for the high‐resolution prospection of upstanding and, especially, buried monuments was limited because of the low resolution of the former sensors. TerraSAR‐X, however, provides us with images with a spatial resolution of up to 1 m. The satellite operates in the so‐called X‐band with a frequency of 9.65 GHz. Therefore it is supposed that there is no possibility to penetrate the soil with this sensor. To testify and analyse the benefit of TerraSAR‐X in archaeological geophysics, we chose as a test site a Roman fortress in Syria. The site was chosen as we already have GPR data of the same area for a comparison and for the verification of the actual penetration depth. Our results revealed that it is possible to resolve superficial and even buried structures in the data set, which provides evidence that the X‐band waves can penetrate the soil. This paper shows our results of the survey and an estimation of the possible penetration depth of TerraSAR‐X. Copyright © 2013 John Wiley & Sons, Ltd.